2001
DOI: 10.3390/60700614
|View full text |Cite
|
Sign up to set email alerts
|

Nitration Of Phenols Under Mild And Heterogeneous Conditions

Abstract: Nitrophenols can be obtained in moderate to high yields using a combination of Mg(HSO4)2 or NaHSO4.H2O, NaNO3 and wet SiO2 in dichloromethane at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 42 publications
0
30
0
2
Order By: Relevance
“…The synthesis of hybrid compounds was accomplished initially by orto-nitration of eugenol (1) and dihydroeugenol (1 ) using sodium nitrate, potassium bisulfate, and wet silica gel in dichloromethane, as reported by Zolfigol and coworkers [16]. These nitroderivatives (2 and 2 ) were obtained in good yields as dark orange oils after successive extractions of the crude material with hexane and solvent evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of hybrid compounds was accomplished initially by orto-nitration of eugenol (1) and dihydroeugenol (1 ) using sodium nitrate, potassium bisulfate, and wet silica gel in dichloromethane, as reported by Zolfigol and coworkers [16]. These nitroderivatives (2 and 2 ) were obtained in good yields as dark orange oils after successive extractions of the crude material with hexane and solvent evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…16 Very recently, we among many others have demonstrated that heterogeneous reagent systems have many advantages such as simple experimental procedures, mild reaction conditions and minimization of chemical wastes as compared to the liquid phase counterparts. [23][24][25][26][27] Thus, inorganic acidic salts such as: Al(HSO4)3 17,18 Mg(HSO4)2 [19][20][21][22][23][24][25] and NaHSO4.H2O [23][24][25][26][27][28][29] could be recommended for above mentioned purposes. Although there are a few reports on the application of these salts in synthetic methodology, but only recently, more attention has been paid to the investigation of their potentials in organic synthesis.…”
mentioning
confidence: 99%
“…Although there are a few reports on the application of these salts in synthetic methodology, but only recently, more attention has been paid to the investigation of their potentials in organic synthesis. [17][18][19][20][21][22][23][24][25][26][27][28][29] Now we wish to report a convenient method for deprotection of acetals or ketals using Al(HSO 4 ) 3 (I), Mg(HSO 4 ) 2 (II) and NaHSO 4 ·H 2 O (III) in the presence of wet SiO 2 (Scheme 1).…”
mentioning
confidence: 99%
“…Also many methods have been reported using metal nitrates as source of nitronium ion. [21][22][23][24][25][26][27][28][29][30] However, these metal nitrates often need extra co-reagents such as phase transfer catalysts or expensive ionic liquids achieve desirable outcomes. Therefore, it is worthwhile to seek for alternative methods that could overcome these problems.…”
Section: Introductionmentioning
confidence: 99%